Nursing interventions in adult psychiatric outpatient care. Making nursing visible using the Nursing Interventions Classification - Maria Ameel; Raija Kontio; Kristiina Junttila (Blackwell Scientific Publications., 2022)
Aim
To describe and to clarify the work of nurses in psychiatric outpatient care using a standardized nursing terminology and to describe the potential benefits and challenges in the use of the terminology.
Design
A qualitative study of ethnographically grounded fieldwork in four adult outpatient units located in three major cities in Finland.
Methods
A two‐phase ethnographically oriented study, consisting of observations and focus group interviews in four psychiatric outpatient care units (in January‐March 2018). During this process, the identified nursing interventions were mapped into the Nursing Interventions Classification.
Results
We identified 93 different nursing interventions, of which 85 were found in the existing terminology, covering all seven domains. Categories describing potential benefits and challenges were: giving words to nurses' work and the challenge of overlapping interventions.
Conclusion
Our findings indicate that the Nursing Interventions Classification is a suitable means to describe nursing in the psychiatric outpatient care setting. Our findings support the theory that describing nurses' work using a nursing terminology can make nursing visible and further empower nurses and help them to structure their work. The lack of other professionals, especially physicians, has led to nurses taking over new tasks officially and unofficially and we suggest that the issue needs to be studied further.
Impact
Nurses' role in the psychiatric outpatient care has been described as invisible and difficult to describe. Our findings suggest that a nursing terminology can make nursing visible, not only from the perspective of patient health records but is also a way to conceptualize nurses' work.